Plant as an alternative source of antifungals against aspergillus infections: a review - Tan, Lee Fang; Yap, Vi Lien; Mogana Rajagopal; Christophe Wiart; Malarvili Selvaraja; Leong, Mun Yee; Tan, Puay Luan (MDPI, 2022)
Aspergillus species consists of a group of opportunistic fungi that is virulent when the immunity of the host is compromised. Among the various species, Aspergillus fumigatus is the most prevalent species. However, the prevalence of fungal infections caused by non-fumigatus Aspergillus has been increasing. Polyenes, echinocandins and azoles are the three main classes of antifungal agents being used for the treatment of aspergillosis. Nevertheless, the incidence of resistance towards these three classes has been rising over the years among several Aspergillus spp. The side effects associated with these conventional antifungal agents have also limited their usage. This urges the need for the discovery of a safe and effective antifungal agent, which presents a major challenge in medicine today. Plants present a rich source of bioactive molecules which have been proven effective against a wide range of infections and conditions. Therefore, this present review intends to examine the current literature available regarding the efficacy and mechanism of action of plant extracts and their compounds against Aspergillus spp. In addition, novel drug delivery systems of plant extracts against Aspergillus spp. were also included in this review.